Prediction of Decision-Making Styles Based on Early Maladaptive Schemas and Coping Strategies in Male and Female University Students - Rahimian, Fatemeh; Yousefpour , Nahid; Bagheri Shiri, Atefeh (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The present study aimed to predict decision-making styles based on early maladaptive schemas and coping strategies among male and female students of the Zand Institute of Higher Education. Methods and Materials: This study employed an applied descriptive-correlational design. The statistical population consisted of all male and female students of the Zand Institute of Higher Education during the study period. Using Cochran’s formula and cluster random sampling, 367 students (285 females and 82 males) were selected as the research sample. Data collection instruments included the Young Early Maladaptive Schema Questionnaire (Young, 1988), the General Decision-Making Styles Questionnaire developed by Scott and Bruce (Scott & Bruce, 1995), and the Endler and Parker Coping Strategies Questionnaire (Endler & Parker, 1990). Data were analyzed using descriptive statistics, Pearson correlation analysis, independent samples t-test, and simultaneous multiple regression analysis through IBM SPSS Statistics. Findings The results indicated that the schema domains of disconnection and rejection (β = .198, p = .018), other-directedness (β = .364, p = .001), and impaired limits (β = .252, p = .002) positively predicted spontaneous decision-making style. Disconnection and rejection (β = .420, p = .001), impaired autonomy (β = .189, p = .010), other-directedness (β = .156, p = .003), and impaired limits (β = .384, p = .001) positively predicted avoidant decision-making style. Disconnection and rejection (β = −.312, p = .001), impaired autonomy (β = −.389, p = .001), and other-directedness (β = −.129, p = .021) negatively predicted intuitive decision-making style. Furthermore, problem-focused coping negatively predicted spontaneous and dependent decision-making styles, whereas emotion-focused and avoidant coping positively predicted maladaptive decision-making styles. Problem-focused coping positively predicted intuitive and rational decision-making styles. Conclusion: The findings demonstrated that early maladaptive schemas and coping strategies play a significant role in explaining adaptive and maladaptive decision-making styles among university students. Maladaptive schemas and ineffective coping strategies were associated with avoidant, dependent, and spontaneous decision-making patterns, whereas problem-focused coping was associated with more adaptive decision-making styles.